Perbaikan Manajemen Pengendalian Mutu Pada Proses Produksi Teh Hitam Berbasis Statistical Quality Control (SQC) - Kara, Dimas Permadi Bagas; Hartono, Ridwan; Wijaya, Dewa Kusuma (Universitas Kadiri, 2026)
PT. XYZ, a black tea factory located in Pemalang Regency, continues to grapple with product defect issues arising during its production process. This study aims to identify the root causes of quality degradation and propose strategic improvements to elevate black tea product standards. The research employs Statistical Quality Control (SQC) techniques, utilizing precise and measurable statistical analysis instruments. Data were assessed descriptively, focusing on quality conditions derived from available records. The quality control stages were executed using various SQC tools, including check sheets, Pareto diagrams, histograms, control charts, and cause-and-effect diagrams (fishbone diagrams). Based on the research findings, out of a total black tea output of 84,380 tons, 4,432 tons of products failed to meet standards, primarily due to non-compliant moisture levels and inconsistent tea leaf sizes. According to the Pareto diagram analysis, the most frequent defect is moisture content non-conformity. This finding confirms that weaknesses in moisture control are the primary factor in quality decline. Recommendations for improvement focus on enhancing moisture control procedures, standardizing harvesting operations, providing labor training, and optimizing the use of quality control tools to significantly reduce defects and strengthen the company's competitiveness in the future.